Fiscal Sustainability in Flow Model: Panel Cointegration Approach for the EU-28 - Radmila Dragutinović Mitrović; Olgica Glavaški; Emilija Beker Pucar (Ovidius University Annals: Economic Sciences Series, 2019)
This paper assesses fiscal sustainability in 28 European Union economies in the period 1995- 2018, using panel cointegration analysis for fiscal sustainability testing. The research is based on econometric framework of nonstationary, heterogeneous, and cross-sectional dependent panels, using robust Westerlund (2007) panel cointegration test, Mean Group, and Pooled Mean Group method of estimations. The results of cointegration analysis for EU-28 point to weak fiscal sustainability, with significant fiscal adjustment in average. However, heterogeneous coefficients show in which economies fiscal sustainability is achieved (whether it is strong or weak fiscal sustainability) and heterogeneous fiscal reactions. Robustness check confirmed existence of fiscal sustainability with heterogeneous fiscal adjustments in European Union economies, and indicated strong fiscal sustainability in the shorter period of time, namely after 1997 when Stability and Growth Pact is introduced.